Exploring Pre-Service EFL Teachers' Beliefs About Their Roles in an Elementary School Classroom in Regard to Pedagogical and Emotional Aspects of Students - Iván Aguirre Sánchez (Asociación Colombiana de Profesores de Ingles, 2014)
This article aims at exploring the beliefs of a group of pre-service teachers from a B.Ed. program in Bilingual Education in Bogotá (Colombia), regarding their role as teachers in some general pedagogical and emotional aspects of their primary school students inside the classroom. They were observed over 16 weeks during their pre-service practice and were asked to submit weekly log entries with pedagogical reflections on their performance. Results show that these pre-service teachers believe motivation and identification of their students' academic needs to be their main role inside the classroom.